Muling magbabalik ang perya The carnival will be back again - Evasco, Eugene Y. (Lampara books, 2013)
"There is this child who, whenever the big summer vacation comes, would go home to the province of his grandfather and grandmother. There, he would spend the summer frolicking in the river, listening to his grandfather's amazing tales, napping under the mango tree on warm afternoons, and sleeping outdoors at night. But what he always looks forward to during the summer is the arrival of the carnival, where he and his grandfather and their dog Bruno are always the first customer. But on his return to the province this summer, his grandfather is already gone. Will he still be able to go to the carnival?"